ON THE USE OF MULTIVARIATE LEVY-STABLE RANDOM FIELD MODELS FOR GEOLOGICAL HETEROGENEITY - Gunning Ja. (My University, 2002)
Increasing attention has been paid to the use of non-Gaussian distributions as models of heterogeneity in sedimentary formations in recent years. In particular, the Levy-stable distribution has been shown to be a useful model of the distribution of the increments of data measured in well logs. Frequently, the width of this distribution follows a power-law type scaling with increment lag, thus suggesting a nonstationary, fractal, multivariate Levy distribution as a useful random field model. However, in this paper we show that it is very difficult to formulate a multivariate Levy distribution with any nontrivial spatial correlations that can be sampled from rigorously in large models. Conventional sequential simulation techniques require two properties to hold of a multivariate distribution in order to work: (1) the marginal distributions must be of relatively simple form, and (2) in the uncorrelated limit, the multivariate distribution must factor into a product of independent distributions. At least one of these properties will break down in a multivariate Levy distribution, depending on how it is formulated. This makes a rigorous derivation of a sequential simulation algorithm impossible. Nonetheless, many of the original observations that spurred the original interest in multivariate Levy distributions can be reproduced with a conventional normal scoring procedure. Secondly, an approximate formulation of a sequential simulation algorithm can adequately reproduce the Levy distributions of increments and fractal scaling frequently seen in real data.
Keywords: HETEROGENEITY; MULTIVARIATE; LEVY; RANDOM FIELD; SEQUENTIAL SIMULATION; INCREMENTS